The role of the Corruption Eradication Commission (CEC) in carrying out its functions and authorities to eradicate corruption - Priyanto, Bambang Budi; Santiago, Faisal; Arief Fakrulloh, Zudan (Jurnal Indonesia Sosial Sains, 2023)
A clean government is a government that is free from the practice of Collusion, Corruption and Nopotism (CCN). Thus, the implementation of clean law and government must be supported by the participation of the community and / or community institutions through the function of control over the implementation of public government and development tasks in an effort to realize good governance. This research includes empirical legal research that uses primary data supported by literature research as secondary data. This research focuses on the function of the KPK's authority in eradicating corruption. The KPK in the Indonesian constitutional structure according to Law Number 19 of 2019 concerning Article 3 of the Corruption Eradication Commission, the Corruption Eradication Commission hereinafter referred to as the Corruption Eradication Commission is a state agency that has executive power that carries out the task of preventing and eradicating Corruption Criminal Acts in accordance with this Law. According to its function, the position of the KPK is equated with the Police and Prosecutor's Office. The KPK is still independent and free from any power. In this provision, what is meant by "any power" is a power that can affect the duties and authorities of the Corruption Eradication Commission or individual members of the Commission from the executive, judiciary, legislature, other parties related to corruption criminal cases, or circumstances and situations or for any reason.